Γ‐Glutamylcysteine alleviates ethanol‐induced hepatotoxicity via suppressing oxidative stress, apoptosis, and inflammation. Issue 10 (13th July 2022) - Liu, Jie; Lu, Shuai; Zhang, Xiaoxue; Zhou, Jinyi; Yan, Xintong; Liu, Huimin; Liang, Juanjuan; Luo, Lan; Zhou, Da; Yin, Zhimin
Abstract: Alcohol abuse is a major cause of alcoholic liver disease (ALD) and can result in fibrosis and cirrhosis. γ‐glutamylcysteine (γ‐GC) is a precursor of glutathione (GSH) with antioxidant and anti‐inflammatory properties. Our research aimed to explore the protective impact of γ‐GC on ALD and its potential mechanisms of efficiency in vitro and in vivo. L02 cells were pretreated with γ‐GC (20, 40, and 80 μM) for 2 h and exposed to ethanol for 24 h. Cell viability, apoptosis, oxidative stress, and inflammatory levels were measured. The expression of protein cleaved caspase‐3 and cleaved PARP and flow cytometry results indicated that γ‐GC decreases apoptosis on L02 cells after ethanol treatment. Moreover, γ‐GC also attenuated oxidative stress and mitochondrial damage in hepatocytes caused by ethanol via increasing cellular GSH, SOD activity, and mitochondrial membrane potential. In vivo experiments, γ‐GC effectively reduced the AST, ALT, and TG levels in mice. The inflammation of ALD was alleviated by γ‐GC both in vivo and in vitro. Additionally, histopathological examination demonstrated that γ‐GC treatment lessened lipid droplet formation and inflammatory damage. In conclusion, these results showed that γ‐GC has anti‐inflammatory and anti‐apoptotic effects on ALD because it could help hepatocytes maintain sufficient GSH levels to combat the excess reactive oxygen species (ROS) generated during ethanol metabolism. Practical applications: Alcohol intake is the fifth highest risk factor for premature death and disability among all risk variables. However, few medicines are both safe and effective for the treatment of ALD. As a direct precursor of GSH, γ‐GC has a broad variety of potential antioxidant and anti‐inflammatory applications for the treatment of numerous medical conditions. In conclusion, these results showed that γ‐GC could protect cells from ALD via suppressing oxidative stress, alleviating inflammation, and preventing apoptosis. Abstract : γ‐GC has a protective effect on ALD via suppressing oxidative stress, alleviating inflammation, and preventing apoptosis.